2021
DOI: 10.3390/scipharm89010005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of 11β-Hydroxysteroid Dehydrogenase Type 1 as Potential Drugs for Type 2 Diabetes Mellitus—A Systematic Review of Clinical and In Vivo Preclinical Studies

Abstract: Diabetes mellitus is a pathology with increasing frequency in society, being one of the main causes of death worldwide. For this reason, new therapeutic targets have been studied over the years. 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) is an enzyme responsible for reducing cortisone to its active form cortisol, which can lead to metabolic changes such as insulin resistance and hyperglycemia. Therefore, 11β-HSD1 inhibition may offer a new therapeutic approach for type 2 diabetes mellitus. This work in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
(121 reference statements)
0
19
0
Order By: Relevance
“…14 It is evident from various reports that increased activity of intracellular glucocorticoids in metabolically active tissues including adipose tissues contributes to the development of metabolic syndrome, particularly insulin resistance and type 2 diabetes. 10,39,40 11β-HSD1 is a bidirectional NDPH-dependent enzyme responsible to interconvert inactive cortisone to its active form cortisol, which in excess can lead to metabolic dysregulations. Studies have shown that the inhibitions of cortisol action using GR antagonist such as 11β-HSD1 inhibitors exhibited ameliorative properties to protect against type 2 diabetes, obesity and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…14 It is evident from various reports that increased activity of intracellular glucocorticoids in metabolically active tissues including adipose tissues contributes to the development of metabolic syndrome, particularly insulin resistance and type 2 diabetes. 10,39,40 11β-HSD1 is a bidirectional NDPH-dependent enzyme responsible to interconvert inactive cortisone to its active form cortisol, which in excess can lead to metabolic dysregulations. Studies have shown that the inhibitions of cortisol action using GR antagonist such as 11β-HSD1 inhibitors exhibited ameliorative properties to protect against type 2 diabetes, obesity and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids such as cortisol are among the ubiquitous hormones that modulate various biological and physiological processes including insulin sensitivity, regulation of energy metabolism, inflammation, stress response, and cardiovascular functions 14 . It is evident from various reports that increased activity of intracellular glucocorticoids in metabolically active tissues including adipose tissues contributes to the development of metabolic syndrome, particularly insulin resistance and type 2 diabetes 10,39,40 . 11β‐HSD1 is a bidirectional NDPH–dependent enzyme responsible to interconvert inactive cortisone to its active form cortisol, which in excess can lead to metabolic dysregulations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations